If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8w+41=-5(w-4)
We move all terms to the left:
-8w+41-(-5(w-4))=0
We calculate terms in parentheses: -(-5(w-4)), so:We get rid of parentheses
-5(w-4)
We multiply parentheses
-5w+20
Back to the equation:
-(-5w+20)
-8w+5w-20+41=0
We add all the numbers together, and all the variables
-3w+21=0
We move all terms containing w to the left, all other terms to the right
-3w=-21
w=-21/-3
w=+7
| 1/3(12x-9)=1 | | 12c=-8+10c | | -6y+6y+30=11 | | 4x+10-5×2=40 | | 12n-18-12n+1=10n | | 1/2(4x+8)=2x+6/2 | | 3x+73=62 | | 7–14x=2x–5 | | (10x-7)+(3x+5)=180 | | 3(2x3)-x=x-23 | | 5f+2=100 | | 4p+8=2p+16 | | -6*8x=-38 | | 4(-5+x)=20 | | 28=12x–36 | | 3/2x=6/x-18 | | 2x+39=1x+64 | | 5(y-2)=7y=-32 | | -56+8h=8 | | 25-3x=134 | | -7+4(4x-8)=76 | | -7m+5+m=41 | | (z−1)=24 | | -4=1+8x-7x | | 5(x+2)=3x=29 | | (7x+4)+(15x-2)=90 | | (4x-20)(2x+30)=180 | | -3(f=8)=39 | | 4(-5x+x)=20 | | 5u+2=2(u-8) | | 2x-2x-10+14=0 | | 3p+14=6 |